2021
DOI: 10.21037/gs-20-783
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hemodynamic instability during laparoscopic pheochromocytoma resection: a retrospective cohort study

Abstract: Background: Adrenalectomy for pheochromocytoma, a rare catecholamine-secreting tumour, is a challenging procedure because of the high risk of intraoperative hemodynamic instability, which can cause life-threatening complications. Our study aimed to identify predictive factors for hemodynamic instability during pheochromocytoma resection as well as to assess the risk factors for postoperative morbidity.Methods: Data of 96 patients, who underwent laparoscopic adrenalectomy were analysed retrospectively.Hemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…There are several plausible explanations for this wide range, including referral biases, differences in the de nition of complications and in the type of complications reported, and importantly, the decade of the performed research as it is known that a signi cant reduction in pheochromocytoma surgical treatment morbidity and mortality has taken place over recent decades [20]. In agreement with our study, series evaluating the severity of complications found similar gures of grade III and IV complications in the Clavien-Dindo score [10][9] [11], although in some series severe complications occurred in up to 31% of the cases [8].…”
Section: Surgical Outcomessupporting
confidence: 84%
See 1 more Smart Citation
“…There are several plausible explanations for this wide range, including referral biases, differences in the de nition of complications and in the type of complications reported, and importantly, the decade of the performed research as it is known that a signi cant reduction in pheochromocytoma surgical treatment morbidity and mortality has taken place over recent decades [20]. In agreement with our study, series evaluating the severity of complications found similar gures of grade III and IV complications in the Clavien-Dindo score [10][9] [11], although in some series severe complications occurred in up to 31% of the cases [8].…”
Section: Surgical Outcomessupporting
confidence: 84%
“…risk factors for postsurgical complications included diabetes [4], tumour size [11], preoperative total urinary metanephrine excretion [7], preoperative systolic blood pressure [7] and open adrenalectomy [12], among others.…”
mentioning
confidence: 99%
“…Bruynzeel and Brunaud indicated that intraoperative SBP above 160 mmHg was a risk factor for HI [ 2 , 8 ] and Aksakal et al revealed that HI was associated with the requirement of cardioactive or vasoactive drugs administration [ 10 ]. Integrating those findings, Pisarska-Adamczyk et al defined HI as an occurrence of both intraoperative episodes of SBP above 160 mmHg and requirement of vasoactive drug administration [ 7 ]. In our study, based on this definition, the hemodynamic parameters including the highest intraoperative BP, incidence of extreme hypertensive episodes, the highest HR and the range of BP fluctuation were significantly higher in the HI group, indicating it could objectively reflect the intraoperative hemodynamic status.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into 2 groups depending on presence or absence of intraoperative HI. As previously described [ 7 ], HI was defined as an occurrence of intraoperative episodes of systolic blood pressure (SBP) above 160 mmHg and vasoactive drug administration.…”
Section: Methodsmentioning
confidence: 99%
“…A low body mass index, large tumor size, coronary heart disease, no preoperative crystal/colloid administration, and intraoperative hemodynamic instability were independent risk factors for cardiovascular morbidity in this cohort [ 64 ]. Another observational study found that the size of the adrenal tumor and diabetes were significant factors for hemodynamic instability [ 65 ]. A very close cardiovascular vigilance in the intensive care unit is encouraged in all postsurgical patients during the immediate postoperative period.…”
Section: Postoperative Carementioning
confidence: 99%